Propuesta de aplicación de las islas flotantes artificiales para la remediación de aguas residuales en las industrias de la provincia de Cotopaxi, 2019. - Villarroel Guayasamin, Juan Pablo (2019)
Cotopaxenses Industries manufacture several products, such as: wood, paper, aluminum, steel, flour, sausages, leather and cement, in during their manufacturing processes there is a large discharge of polluted water which affects and alter the quality of Cutuchi River. This research proposed the implementation of the Artificial Floating Islands System (IFAS) in the industries of Cotopaxi Province, as a low-cost alternative and easy-to-maintain of wastewater. For applying this proposal, a diagnosis was carried out on the management of water, carried out by 11 Industries of Cotopaxi. Historical results of water pollution concentrations generated by water pollution. With the information obtained, IFAS was proposed in number of structures and remedial species for each type of industry. In the wood industry the installation proposal is 5 to 6 floating structures for heavy metal removal with Vetiveria zizanioides; in the dairy industries, 5 floating structures with Canna indica and Panicum maximum will be installed which will help the removal of nitrates, phosphates and organic matter, in the leather industry 2 floating structures for the removal of nitrates will be installed, phosphates and chromium with Canna indica, in the steel industry 4 floating structures for the removal of heavy metals with Vetiveria zizanioides will be installed, in the sausage production industry 46 structures for the removal of nitrates and phosphates with Canna indica and Vetiveria zizanioids.